Consultation and contest: the danger of mixing modes - Kane, John; Bishop, Patrick (2002)
This paper argues that public consultative procedures undertaken by governments or their public services sometimes go awry because of certain confusions as to the nature and purposes of consultation. One of the most important of these is a tendency to view consultation as an exercise in policy determination by the public rather than as public input into the representative democratic process whose ultimate use is to be defined by the elected decision-makers. The result of this confusion is a tendency to misunderstand or overestimate what public consultations can achieve, and a failure to make a distinction between occasions when such consultations are useful and occasions when they must give way to explicit political contest. Three levels of activity - the technical, the transactional and the political - are analytically distinguished along with the modes of action-response appropriate to each - in order to explain and clarify the nature of good consultative practice. - Reproduced.
Keywords: Policy making